LAW ENFORCEMENT IN THE INDONESIAN CONSTITUTIONAL SYSTEM IS IN ACCORDANCE WITH THE LAW THE ENFORCER’S CONSCIENCE - Kholifah, Aisyah Fitri; Yahya, Farich Johandi (International Journal of Social Service and Research, 2024)
The purpose of this research is to analyze and evaluate the role of law enforcement in the Indonesian constitutional system, specifically focusing on how the enforcement of laws aligns with the personal conscience and ethical judgment of law enforcers. The study utilizes secondary data gathered through literature reviews, drawing from primary, secondary, and tertiary legal materials, such as legislation, books, journals, and articles. The collected data is analyzed following the Miles and Huberman (2014) model, which includes processes of data reduction, data display, and data verification, to derive conclusions pertinent to the research questions. It sheds light on how ethical considerations influence decision-making, offering insights into the moral dimensions of the law enforcement beyond formal legal frameworks. Furthermore, this study contributes to discussions on judicial integrity and accountability, providing a foundation for evaluating how personal conscience impacts the fairness and effectiveness of law enforcing. It also offers practical recommendations for strengthening the ethical standards and professional judgment of judicial officials in Indonesia. Comparative studies on how different countries' judicial systems integrate human rights and democratic values into their law enforcement structures could provide valuable insights for reforming Indonesia's judicial system to meet global standards of justice and fairness.